1994
DOI: 10.1143/jjap.33.4154
|View full text |Cite
|
Sign up to set email alerts
|

On Schlomilch's Integral Equation for the Ionospheric Plasma

Abstract: The analytical form of the absorption index appropriate to the D- and E-region of the ionospheric plasma is derived. It has been utilised to build up Schlomilch's integral equation. The corresponding solution is obtained in terms of certain ionospheric parameters. The variation of effective collision frequency with height has been computed numerically from the derived solution. The results are presented graphically along with an earlier work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Unz (1966) and Gething and Maliphant (1967) used the Schlömilch's integral equations to described the ionosphere electron profile in a closed form. De et al (1994) derived an analytic form of the absorption index of the ionospheric plasma. They used it to build up the Schlomilch's integral equations.…”
Section: Introductionmentioning
confidence: 99%
“…Unz (1966) and Gething and Maliphant (1967) used the Schlömilch's integral equations to described the ionosphere electron profile in a closed form. De et al (1994) derived an analytic form of the absorption index of the ionospheric plasma. They used it to build up the Schlomilch's integral equations.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important and useful equation in atmospheric and terrestrial physics. For the derivation and applications of the equation in physics, we refer the reader to [1][2][3][4][5][6][7]. The standard linear Schlömilch's integral equation has an unknown function with a complicated argument and admits the following form: It's been shown that this equation provides a solution which has the following form:…”
Section: Introductionmentioning
confidence: 99%